The Glutamine Transporter Slc38a1 Regulates GABAergic Neurotransmission and Synaptic Plasticity - Qureshi, Tayyaba (Cereb Cortex, 2019)
GABA signaling sustains fundamental brain functions, from nervous system development to the synchronization of population activity and synaptic plasticity. Despite these pivotal features, molecular determinants underscoring the rapid and cell-autonomous replenishment of the vesicular neurotransmitter GABA and its impact on synaptic plasticity remain elusive. Here, we show that genetic disruption of the glutamine transporter Slc38a1 in mice hampers GABA synthesis, modifies synaptic vesicle morphology in GABAergic presynapses and impairs critical period plasticity. We demonstrate that Slc38a1-mediated glutamine transport regulates vesicular GABA content, induces high-frequency membrane oscillations and shapes cortical processing and plasticity. Taken together, this work shows that Slc38a1 is not merely a transporter accumulating glutamine for metabolic purposes, but a key component regulating several neuronal functions.